The determinants of export : evidence from OECD countries (2008-2017) / Noor Nabilah Abdul Wahab - Abdul Wahab, Noor Nabilah (2020)
The aim of this study is to determine the export in OECD countries. The dependent variable of this study is export while the independent variables are gross domestic product, inflation, foreign direct investment and import. The data used in this study is panel data. The sample of study consists of 6 OECD countries and data collected over the period from 2008 until 2017. This current study employs Panel Regression Fixed Effect Model in examining the relationship between those variables. The result of this study shows that gross domestic product has negative significant relationship with export. In addition, inflation has positive relationship with export. However, import have positive significant impact on export.